Lithospheric structure beneath the northern Central Andean Plateau from the joint inversion of ambient noise and earthquake‐generated surface waves. Issue 11 (25th November 2016) - Ward, Kevin M.; Zandt, George; Beck, Susan L.; Wagner, Lara S.; Tavera, Hernando
Abstract: The Central Andean Plateau (CAP), as defined by elevations in excess of 3 km, extends over 1800 km along the active South American Cordilleran margin making it the second largest active orogenic plateau on Earth. The uplift history of this high Plateau, with an average elevation around 4 km above sea level, remains uncertain as paleoelevation studies along the CAP suggest a complex, nonuniform uplift history. As part of the Central Andean Uplift and the Geodynamics of High Topography (CAUGHT) project, we image the S wave velocity structure of the crust and upper mantle using surface waves measured from ambient noise and teleseismic earthquakes to investigate the upper mantle component of plateau uplift. We observe three main features in our S wave velocity model including (1) a positive velocity perturbation associated with the subducting Nazca slab; (2) a negative velocity perturbation below the sub‐Andean crust that we interpret as anisotropic Brazilian cratonic lithosphere; and (3) a high‐velocity feature in the mantle above the slab that extends along the length of the Altiplano from the base of the Moho to a depth of ~120 km. A strong spatial correlation exists between the lateral extent of this high‐velocity feature and the relatively lower elevations of the Altiplano basin suggesting a potential relationship. Determining if this high‐velocity feature represents a small lithospheric root or foundering of orogenic lithosphere requires more integration of observations, but either interpretation implies a strong geodynamic connection with the uppermost mantle and the current topography of the northern CAP. Key Points: Lithospheric scale S wave velocity model for the northern Central Andean Plateau We image a well‐resolved subducting Nazca slab and anisotropic Brazilian cratonic lithosphere Fast‐velocity anomaly below the Altiplano suggests a geodynamic connection with modern topography